Diversity research and policy : a multidisciplinary exploration - Knotter, Steven (Pallas Publications, 2011)
This volume has emerged out of a collaborative Network of Excellence (NoE) project funded by the European Commission. The NoE is designed to strengthen excellence on 'Sustainable Development in a Diverse World'. It integrates European research capabilities across disciplines and countries to provide society and polity with tools for managing cultural diversity as a key element of sustainable development. The Network comprises 32 institutes from Europe and beyond. It has lead to a growing realization that scholars and practitioners need to be aware of each other's intellectual inspiration when approaching the relationship between cultural diversity and sustainable development.